Investigation of infiltration rate on soft claythat affecting the ponding time - Adnan, Mohd Shalahuddin; Mohd Anuar, Mohd Aliff; Nda, Muhammad; Rahmat, Siti Nazahiyah (EDP Sciences, 2017)
Malaysia is a country that has abundant rainfall that depends on the seasonal such as monsoon, where,certain areas in peninsular area are expected to receive heavy rain during this monsoon season. This abundant of rain could lead to massive flood if no mitigation actions were taken. One of the factor that contribute to the flood occurrences is type of soils. Type of soils play an important role in determining the rate of infiltration. Thus, this study was conducted to investigate the infiltration rate that effecting the ponding time at the Universiti Tun Hussein Onn Malaysia (UTHM). This area is located at flat topography with thick layer of clay soil beneath the ground surface that indicated low infiltration capacity rate. This condition could causeponding of water that could lead to high surface runoff that could cause flood.This paper was aimed at understanding the effect of soil clay layer on infiltration rate and ponding time. Infiltration test was conducted at four (4) points to make a spatial analysis around the study area. The soil was classified based on soil classification system (USCS), while, ponding time was calculated based on Horton model. Based on the results, the average infiltration rate is ranging from 0.004 mm/s to 0.076 mm/s among the selected locations.Soil samples were sieve and thedominant soil comprises of minimal well graded silty clay and clayey sand which is more than 50% content sand and more than 12% content fines. Lastly, time of ponding was calculated by using Horton model and it shows that the ponding time started between 0.51h to 1.0h. This information could serve a vital information on determining the mitigation measures to tackle a flood problem in this area.